Return of education and retirement age decision: a case study among management graduates from Malaysia - Loganathan, Nanthakumar; Mohd Noor, Zaleha; Abd Jalil, Suhaila (The Publisher, 2013)
In this study we propose a simulation approach using Cost and Benefit Analysis (CBA) to evaluate effects of the increase in retirement age on education return among tertiary management graduates in Malaysia. All data are computed into CBA model using simulation approach to measure the Internal Rate of Return (IRR) once the retirement age is increased yearly. The overall findings of this study show that the IRR is not sensitive to the assumption made about the retirement age decisions; and the IRR does not change from the compulsory retirement age proposed by the Malaysian government. Therefore, the 56 years for retirement age for management graduates in Malaysia is still ideal in term of education return.